ELECTRONIC DOCUMENT FOR RESEARCH AND SERVICE WITH WEB-BASED IN HIGHER EDUCATION (CASE STUDY: LP4M IIB DARMAJAYA) - Nursiyanto Nursiyanto; Sri Karnila; Ronaldo Ronaldo (Jurnal TAM (Technology Acceptance Model), 2020)
This research produces information on e-data for research and community service, which can help the administration department at LP4M IIB Darmajaya. The current problem is that submission of research proposals and community service by the proposing lecturer or researcher is carried out conventionally, i.e. not referring to the paperless concept, submitting proposal files, administrative inspection processes, filing not having a special database, so it is ineffective and efficient. The waterfall method through the stages of needs analysis, design, coding, and testing, e-data information can help LP4M management. The proposer or researcher can upload with a template, the reviewer can evaluate the proposal, the results of the review are informed to the researcher, and inform whether the proposal is accepted or not. Super admin of LP4M, can inform, update, coordinate, and organize documentation. Another benefit of this system is that the faculty or other management department requires information related to research data and service data as forms that can be downloaded through the system. This shows that the performance of e-data increases the productivity of research and service document administration that can be utilized by the Darmajaya academic community.